Tamoxifen Exposure during Pregnancy: A Systematic Review and Three More Cases - Buonomo, Barbara (Breast Care (Basel), 2020)
Tamoxifen is frequently used as adjuvant treatment in premenopausal patients with hormone receptor-positive early breast cancer. According to guidelines, the use of nonhormonal barrier contraception is recommended during tamoxifen treatment and up to 3 months after its interruption prior to attempting conception. Nevertheless, when conception occurs inadvertently during tamoxifen treatment, the effects on the fetus and on the course of pregnancy are still not completely known. Here, we report 3 cases of young women who accidentally became pregnant while taking tamoxifen and perform a systematic review of the literature to provide more elements for better and clear multidisciplinary counselling of women facing this challenging situation.